2024
DOI: 10.1021/acsnano.3c09935
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite Nanocrystals Induced Core–Shell Inorganic–Organic Nanofibers for Efficient Energy Harvesting and Self-Powered Monitoring

Chuanwei Zhi,
Shuai Zhang,
Hanbai Wu
et al.

Abstract: The emerging field of wearable electronics requires power sources that are flexible, lightweight, highcapacity, durable, and comfortable for daily use, which enables extensive use in electronic skins, self-powered sensing, and physiological health monitoring. In this work, we developed the core−shell and biocompatible Cs 2 InCl 5 (H 2 O)@PVDF-HFP nanofibers (CIC@HFP NFs) by one-step electrospinning assisted self-assembly method for triboelectric nanogenerators (TENGs). By adopting lead-free Cs 2 InCl 5 (H 2 O)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Energy harvesting from ubiquitous sources has attracted a lot of interest in the present day to meet the increasing demand for renewable energy. Among the various techniques of energy harvesting, triboelectric nanogenerators (TENG) are considered promising due to the abundance in the selection of materials, ease of use, and appreciable power density offered by such devices. A variety of TENGs have been reported that are capable of harvesting energy from simple human motions, , wind, and water droplets . However, to power wearable and portable small-scale electronic devices, TENGs that can be effortlessly integrated into clothing are required. For such reason, textile-based TENGs have also attracted much interest. …”
Section: Introductionmentioning
confidence: 99%
“…Energy harvesting from ubiquitous sources has attracted a lot of interest in the present day to meet the increasing demand for renewable energy. Among the various techniques of energy harvesting, triboelectric nanogenerators (TENG) are considered promising due to the abundance in the selection of materials, ease of use, and appreciable power density offered by such devices. A variety of TENGs have been reported that are capable of harvesting energy from simple human motions, , wind, and water droplets . However, to power wearable and portable small-scale electronic devices, TENGs that can be effortlessly integrated into clothing are required. For such reason, textile-based TENGs have also attracted much interest. …”
Section: Introductionmentioning
confidence: 99%